Rancang Bangun Sistem Monitoring Particulate Matter (PM2.5) dan Karbon Monoksida di Poliklinik Universitas Brawijaya Berbasis IoT - Muslimin, Nurhaliza; Maulana, Eka; Nurussa’adah, n/a (Jurnal Mahasiswa TEUB, 2024)
Air pollution occurs in almost every city in Indonesia. The high levels of particulate and harmful gas pollution exceeding the national standards of 15 µg/m³ for Particulate Matter (PM2.5) and 35 ppm for carbon monoxide can have serious impacts on the health and life expectancy of Indonesia's 272 million population. This research responds to this challenge by designing a monitoring system capable of detecting levels of PM2.5 and carbon monoxide in the environment of the University of Brawijaya Polyclinic. Increasing awareness of the importance of healthy air quality makes monitoring particulate and gas levels a crucial need, especially in healthcare facilities. Using Internet of Things (IoT) technology, this system is developed to provide real-time monitoring of air quality through a web based Blynk dashboard that is easily accessible by clinic staff. The system's composition involves the GP2Y1010AU0F sensor for particulate detection, the MQ-9 sensor for measuring carbon monoxide gas concentration, and the DHT22 sensor for measuring room temperature and humidity. The system also provides an alert system with indicator lights when PM2.5 and CO concentrations reach unsafe levels, as well as a mist maker for air quality maintenance. The results of this research show that the designed system operates stably and provides accurate data with error rates of 0.62% for the GP2Y1010AU0F sensor, 1.73% for the MQ-9 sensor, and 0.98% for temperature measurement and 1.07% for humidity measurement using the DHT22 sensor. Keywords: The Brawijaya University Policlinic, PM2.5, carbon monoxide, temperature and humidity, air quality, Blynk